Análisis del proceso de verificación de origen en el acuerdo de complementación económica 59 aplicado por el eEuador para las importaciones de calzado brasileño y su incidencia en las nacionalizaciones tramitadas por la Agencia Aduanera Uquillas - García Uquillas, Jorge Santiago (2021)
The main objective of the investigation is to analyze the origin verification process in the Economic Complementation Agreement 59 that Ecuador applies to imports of Brazilian footwear. This with the intention of describing the incidence of this commercial instrument on the costs and processes of nationalization executed by the Uquillas customs agency located in the city of Quito in the province of Pichincha. The methodology corresponded to a descriptive and correlational research, with a mixed approach. Surveys were used as a means of gathering information, applied to importers of footwear managed by the selected customs agent. The results reveal, among other things, that ACE 59 has had a positive influence on the growth of the commercial relationship between Ecuador and Brazil, mainly in those tariff subheadings stipulated in the agreement in question………..